Organocatalytic Enantioselective 1, 6‐aza‐Michael Addition of Isoxazolin‐5‐ones to p‐Quinone Methides. Issue 5 (27th January 2020) - Torán, Ricardo; Vila, Carlos; Sanz‐Marco, Amparo; Muñoz, M. Carmen; Pedro, José R.; Blay, Gonzalo
Abstract : A thiourea‐Brønsted base bifunctional catalyst allowed the enantioselective 1, 6‐ aza ‐Michael addition of isoxazolin‐5‐ones to p ‐quinone methides to give isoxazolin‐5‐ones having a chiral diarylmethyl moiety attached to the N atom with fair to good yields and enantiomeric excesses. To the best of our knowledge this reaction represents the first example of enantioselective N ‐alkylation of isoxazolin‐5‐ones as well as the first example of enantioselective 1, 6‐ aza ‐Michael reaction involving p ‐quinone methides. Abstract : A bifunctional organocatalyst allowed the enantioselective 1, 6‐ aza ‐Michael addition of isoxazolin‐5‐ones to p ‐quinone methides to give isoxazolin‐5‐ones having a chiral diarylmethyl moiety attached to the N atom with fair to good yields and enantiomeric excesses.